Academic Cultural Study of Reading Interest in State Madrasah Aliyah Jambi City - Miliani, Masyrisal; Riady, Yasir; Husna, Nailul; Siswanto, Achmad (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to describe the challenges and efforts of educational institutions in developing an academic culture of interest in reading in their students. This research uses a qualitative approach with the case study method as a strategy of inquiry. The focus and subjects of the research were among madrasa heads, teachers, and students at three State Madrasah Aliyahs in Jambi City. Primary data was collected by distributing questionnaires, in-depth interviews and observations. Meanwhile, secondary data was collected through extensive document study. This research shows that the academic and cultural challenges of interest in reading in the three state aliyah madrasahs in Jambi City are almost the same, namely the lack of monitoring of reading habits in the madrasah arena. Even though madrasas face challenges, efforts to develop an academic culture of interest in reading continue to be carried out in each madrasa in Jambi City.